ENTREPRENEURIAL MANAGEMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS: CONCEPTS, PRACTICES, AND FUTURE DIRECTIONS - Yusuf Effendi; Achmad Zailani; Yetri Yetri; Badarudin Badarudin (STKIP Pesisir Selatan, 2026)
Entrepreneurial management has become a strategic issue for Islamic educational institutions as they are increasingly expected to strengthen student independence, institutional sustainability, ethical leadership, and community empowerment. This study aims to synthesize the concepts, practices, novelty, and future directions of entrepreneurial management in Islamic educational institutions. Using an integrative review design, this study examined peer-reviewed literature published between 2020 and 2025 and analyzed ten selected articles after a screening process from 154 initial records. The selected articles were reviewed through inclusion and exclusion criteria, full-text eligibility assessment, structured data extraction, and thematic synthesis. The findings reveal that entrepreneurial management in Islamic educational institutions consists of five interconnected dimensions: Islamic value-based governance, entrepreneurial leadership, practice-oriented entrepreneurship education, stakeholder-based institutional sustainability, and digital or startup-oriented development. The review shows that entrepreneurship in Islamic education is not merely an economic activity or business training program, but an institutional management strategy that integrates Islamic values, curriculum innovation, business-unit development, alumni involvement, and external collaboration. The novelty of this study lies in its integrative framework that distinguishes entrepreneurship education as a pedagogical process from entrepreneurial management as a broader institutional capacity. The findings imply that Islamic schools, madrasahs, pesantren, and Islamic educational startups need to position entrepreneurship as part of strategic governance to enhance innovation, financial resilience, student employability, and socially responsible educational transformation.